Diuretic properties of Orthosiphon stamineus Benth. - Adam, Yunus; M. N., Somchit; Sulaiman, Mohd Roslan; Abdul Aziz, Nasaruddin; Ahmad, Zuraini; Abdul, Ahmad Bustamam; Zakaria, Zainul Amiruddin (Elsevier, 2009)
Ethnopharmacological relevance: Orthosiphon stamineus has been used in traditional medicine for centuries especially to treat diseases of the urinary system.